The Real War - Nixon, Richard; With a new introduction by Nixon, President (New York Simon & Schuster, 1990)
In this landmark 1980 bestseller, Nixon presents a trenchant analysis of East-West relations & a prescription for renewed strength. "Provocative...striking...it says publicly what many foreign policy specialists dare not reveal."
Include Notes and Index.
Keywords: Diplomatic relations -- United States -- World politics